2019
DOI: 10.1094/phyto-06-18-0213-r
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Resistance Mechanism in Brassica napus to Clubroot Caused by Plasmodiophora brassicae

Abstract: Exploring the mechanism of plant resistance has become the basis for selection of resistance varieties but reports on revealing resistant mechanism in Brassica napus against Plasmodiophora brassicae are rare. In this study, RNA-seq was conducted in the clubroot-resistant B. napus breeding line ZHE-226 and in the clubroot-susceptible rapeseed cultivar Zhongshuang 11 at 0, 3, 6, 9, and 12 days after inoculation. Strong alteration was detected specifically in ZHE-226 as soon as the root hair infection happened, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Many studies conducted to date have focused on molecular mechanisms aided by “-omics” approaches, such as RNA-seq. Mei et al (2019) reported great differences between two rapeseed genotypes, especially in the activation of signaling networks, the production of reactive oxygen species (ROS) and the programmed cell death (PCD) response to P. brassicae ( Mei et al, 2019 ). Chu et al (2014) found that the genes involved in the jasmonate (JA) and ethylene (ET) signaling and metabolic pathways and the defensive deposition of callose were significantly upregulated in clubroot-resistant plants compared to their levels in susceptible lines at 15 days after infection ( Chu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies conducted to date have focused on molecular mechanisms aided by “-omics” approaches, such as RNA-seq. Mei et al (2019) reported great differences between two rapeseed genotypes, especially in the activation of signaling networks, the production of reactive oxygen species (ROS) and the programmed cell death (PCD) response to P. brassicae ( Mei et al, 2019 ). Chu et al (2014) found that the genes involved in the jasmonate (JA) and ethylene (ET) signaling and metabolic pathways and the defensive deposition of callose were significantly upregulated in clubroot-resistant plants compared to their levels in susceptible lines at 15 days after infection ( Chu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…PTI is involved in the induction of plant hormone signal transduction and plant-pathogen interaction at the late stage of B. rapa resistant lines containing the CRd gene when exposed to P. brassicae [28]. In contrast, in the B. rapa near-isogenic line (CR BJN3-2) and B. napus resistance line (ZHE-226), no significant changes were detected when compared with the susceptible lines after inoculation with P. brassicae [13,15]. In this study, in comparison, we could not detect a significant interaction between the host and pathogen in the first defense mechanism, which might be due to pathogen effector proteins which have evolved to suppress the PTI; however, further study is required.…”
Section: Plant-pathogen Interactionmentioning
confidence: 99%
“…ROS is a well-known secondary messenger in cellular processes, and RBOHs are critical enzymes that produce ROS in response to hormonal and environmental signals and are activated by Ca 2+ [42,43]. ROS-associated signaling that suppresses pathogen growth determines PCD and HR [15]. It also works with other signaling molecules and induces SA and its regulators, the NPR1 and TGA transcription factors [44], and ROS-mediated defense plays a central key role in cross-talk with other molecular mechanisms, having great potential for resistant genotype selection [45].…”
Section: Defense Signaling Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of time-scale transcriptome analysis revealed that functional ETI (effector triggered immunity) responses rely on an appropriate time point for transcriptional reprogramming, which is mediated by jasmonate, ethylene, salicylic acid, and PAD4 signaling (19). Transcriptome analysis provided useful information for understanding the resistance mechanism of Brassica napus to clubroot disease (20) and was performed to investigate the regulatory mechanism of Pi9 and Pi21, two R (resistance genes) that control blast fungus (21,22).…”
mentioning
confidence: 99%